Preliminary results of intrahospital HCV screening for elimination: A single center experience. (March 2023) - Costa, E. Garlatti; Moratto, A.; Da Re, M.; Villalta, D.; Pirrone, F.; Passadore, P.; Ubiali, P.; Tonizzo, M.
Abstract : Introduction: New HCV models of care aimed to elimination are emerging. In particular, hospitalized patients may represent an ideal population for HCV screening and for referral treatment. Aim: To evaluate the feasibility of an opportunistic hospital-based HCV screening and its linkage to care in our Hub Hospital Pordenone (Friuli Venezia Giulia). Methods: All patients consecutively admitted to Internal Medicine, Neurology, Gynecology and Surgery from 5.09.2022 to 5.12.2022 were screened with in-hospital reflex HCV testing. During the hospital stay, Hepatologysts examined all viremic subjects, as the result of Laboratory alert or Specialist advice. Results: Among 1.176 (median age: 70 years old, 59% female) inpatients consecutively screened, 40 (3.4%) were HCV-Ab positive. Among patients positive for HCV-Ab, 9 had been previously treated for HCV infection with SVR and were excluded. Of 31 patients (HCV-Ab+) patients who were tested for HCV-RNA, 15 (1.2%) were HCV-RNA positive. The highest prevalence of HCV-RNA positivity (86%) was found in patients admitted to Internal Medicine. Of 15 patients HCV-RNA+: 2 patients died during hospital admission, 1 refused treatment with DAAs, 7 patients were evaluated for antiviral therapy but were excluded due to severe comorbidities, short life expectancy (<6 months) and elderly age, 2 (13%) patients started DAAs. Antiviral treatment was planned for the remaining 3 patients, after the resolution of the acute event that led to hospitalization (sepsis, pneumonia, heart failure). For all patients with hepatitis C, HCV counselling for caregivers was explained. 5 patients (33%) were unaware of HCV infection. Conclusions: Hospital HCV screening is feasible because HCV active infection has been frequently found in patients with comorbidities admitted in our Hospital.In fact submerged/unaware people with hepatitis C still exist. In-hospital reflex HCV testing has enabled optimal linkage to care for the first visit. However, reasons for hospital admission and severe comorbidities may delay antiviral treatment reducing the HCV treatment cascade.